Realizing the Value of a National Asset: Scientific Data. Issue 50 (16th December 2014) - Wilson, Anne; Downs, Robert R.; Lenhardt, W. Christopher; Meyer, Carol; Michener, William; Ramapriyan, Hampapuram; Robinson, Erin
<x xml:space="preserve">Abstract</x> "We have a shared responsibility to create and implement strategies to realize the full potential of digital information for present and future generations, " according to the Electronic Geophysical Year (eGY) Declaration [CoBabe‐Ammann et al., 2007]